Binding of the EcoRII methylase to azacytosine-containing DNA. - Friedman, S (1986)
Binding of DNA(cytosine-5)methyltransferases to azacytosine containing DNA is stimulated by the presence of S-adenosyl-methionine or its analogs sinefungin or S-adenosyl-L-homocysteine. Methylation of the DNA is therefore not necessary for binding to occur. There is no relationship between the affinity of the analog for the EcoRII enzyme and its ability to stimulate binding. The DNA-enzyme complex partially dissociates on incubation in 0.1% sodium dodecyl sulfate and 0.5 M ammonium acetate. Some of this DNA could again form a tight complex with enzyme, indicating that DNA-enzyme complex formation is reversible. Binding occurs when the second cytosine in the sequence CCAGG is substituted by azacytosine. This is the cytosine that would normally be methylated by the enzyme. The binding is therefore due to specific interaction of the methylase with azacytosine at the site it would normally methylate.